Considering the Effect of Holes Distances of Beam Flanges on Seismic Behavior of Drilled Flange (DF) Connections - Mohsen Alibakhshi (Journal of Structural and Construction Engineering, 2015)
Reduced beam section (RBS) connection has known as a qualified rigid connection regarding AISC(2010) with acceptable ductility for Special Moment Resisting Frames (SMRF). Beam to column welded Connection with radius cut on beam flange is categorized as RBS connection in AISC(2010) code. In order to decrease the cost of construction and provide an easy-to-construct rigid connection, a new connection, which is called drilled flange connection (DFC), has been suggested in this study to reduce the stress concentration  on column flange.  DFC is established by a series of holes drilling on top and bottom beam flange. In this research, based on detail validated Finite element models, some parametric FEMs were created to study the effect of holes configurations on the beam flanges. This study showed that the acceptable connections performance for DFC  regarding AISC(2005) code will provided if the specific holes configuration with definite distances between the holes ,which have the specific ranges depending  on the beam depth, is  allocated  to reduce the analytical rupture indices on beam to column welded connection as critical points. Furthermore the results indicated that uniform and non uniform holes configurations have the same analytical rupture Indies on critical points thus uniform holes configuration is recommended because of easier construction.